2011
DOI: 10.1039/c0an00952k
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous control of spectroscopic and electrochemical properties in functionalised electrochemiluminescent tris(2,2′-bipyridine)ruthenium(ii) complexes

Abstract: Using a combination of electrochemical, spectroscopic and computational techniques, we have explored the fundamental properties of a series of ruthenium diimine complexes designed for coupling with other molecules or surfaces for electrochemiluminescence (ECL) sensing applications. With appropriate choice of ligand functionality, it is possible to manipulate emission wavelengths while keeping the redox ability of the complex relatively constant. DFT calculations show that in the case of electron withdrawing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 71 publications
4
52
0
Order By: Relevance
“…The reductions associated with 2 occur at more negative potentials than 1 , probably due to the electron‐withdrawing effect of the carboxylic group compared to the ester. The irreversible electrochemistry associated with complex 2 is a consequence of the presence of a carboxylic acid moiety, as observed for other polypyridyl ruthenium complexes containing such groups …”
Section: Resultsmentioning
confidence: 70%
“…The reductions associated with 2 occur at more negative potentials than 1 , probably due to the electron‐withdrawing effect of the carboxylic group compared to the ester. The irreversible electrochemistry associated with complex 2 is a consequence of the presence of a carboxylic acid moiety, as observed for other polypyridyl ruthenium complexes containing such groups …”
Section: Resultsmentioning
confidence: 70%
“…For the complexes considered here, plots of the frontier MOs are given in Figure and S6. The MOs of [Ru(bpy) 3 ] 2+ are already well characterized, with a metal‐centered HOMO and ligand‐based LUMO . The triplet‐state spin density (Figure and S7) shares the same spatial extent as the singlet HOMO and LUMO, for which the lowest singlet‐triplet transition may be described as metal‐to‐ligand charge‐transfer (MLCT) .…”
Section: Resultsmentioning
confidence: 99%
“…For these multi‐luminophore experiments, we replaced [Ru(bpy) 3 ] 2+ with [Ru(bpy) 2 (L)] 2+ (L= N 4 , N 4′ ‐bis((2S)‐1‐methoxy‐1‐oxopropan‐2‐yl)‐2,2′‐bipyridyl‐4,4′‐dicarboxamide)). The electron‐withdrawing amide groups of this complex impart a bathochromic shift ( λ max =666 nm),18 which provides much greater spectral separation from [Ir(ppy) 3 ] (Figure S3 in the Supporting Information). Although the amide groups also influence the ground and excited state redox properties (e.g., [Ru(bpy) 3 ] 2+ *: E ox =−1.22 V and E red =+0.36 V, whereas [Ru(bpy) 2 (L)] 2+ *: E ox =−0.90 V and E red =+0.39 V vs Fc 0/+ ),6h, 18 the differences are small when compared to the properties of [Ir(ppy) 3 ]* (see above), and it is the much greater reducing ability of the excited [Ir(ppy) 3 ]* species that renders it vulnerable to oxidative quenching.…”
Section: Resultsmentioning
confidence: 99%
“…The electron‐withdrawing amide groups of this complex impart a bathochromic shift ( λ max =666 nm),18 which provides much greater spectral separation from [Ir(ppy) 3 ] (Figure S3 in the Supporting Information). Although the amide groups also influence the ground and excited state redox properties (e.g., [Ru(bpy) 3 ] 2+ *: E ox =−1.22 V and E red =+0.36 V, whereas [Ru(bpy) 2 (L)] 2+ *: E ox =−0.90 V and E red =+0.39 V vs Fc 0/+ ),6h, 18 the differences are small when compared to the properties of [Ir(ppy) 3 ]* (see above), and it is the much greater reducing ability of the excited [Ir(ppy) 3 ]* species that renders it vulnerable to oxidative quenching. We have found that even a small decrease in the reducing ability, such as when a single fluorine group is added to the phenyl ring of one ligand, lessens the degree of the ‘switch off’ of ECL (Figure S5 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%